MICROBLOG VIDEO PROJECT AND MEANINGFULL LEARNING MEDIUM TO PROMOTE UNIVERSITY STUDENTS’ 4CS IN THE 21ST CENTURY OF EFL LEARNING - Ni Putu Intan Permatasari (Jurnal Scientia, 2023)
Learning activities conducted in the classrooms are essential to attain students‟ comprehension and participation in the learning process. The efforts to acquire students‟ engagement in the class activities are totally assisted by the advancement and rapid growth of digital technology. The digital has put more load on the integration of technology in teaching and learning process. The university lecturers do not only need to master the content and pedagogical knowledge but also, involve a provision to integrate those two components with technology. It is aimed to create a meaningful learning in the 21st century learning environment. The integration of technology can also promote students‟ digital literacy and the importance of 4Cs competences in the 21st century of English as Foreign Language (EFL) learning. This study is intended to investigate the Microblog Video Project as a Meaningful Learning Media to enhance university students‟ comprehension in EFL learning. The microblog video project was focused on students‟ speaking, writing, listening, and reading skills in describing global issues and also the implementation of 4Cs. This study employed a descriptive qualitative approach with classroom observation and a semi-structured interview conducted to 15 students who have had a microblog video project as their middle test in General English class at Universitas Pendidikan Nasional (Undiknas University) Denpasar, Bali. The results of this study revealed that the microblog video project has advantageous impacts for students in their learning process on EFL learning holistically.